2010
DOI: 10.1080/13647830.2010.490881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of equivalence ratio variation on lean, stratified methane–air laminar counterflow flames

Abstract: The effects of equivalence ratio variations on flame structure and propagation have been studied computationally. Equivalence ratio stratification is a key technology for advanced low emission combustors. Laminar counterflow simulations of lean methaneair combustion have been presented which show the effect of strain variations on flames stabilized in an equivalence ratio gradient, and the response of flames propagating into a mixture with a time-varying equivalence ratio. 'Back supported' lean flames, whose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 33 publications
5
32
0
Order By: Relevance
“…the instantaneous flame front resides at approximately φ=0.7 in all cases) the difference in burning intensity is attributed to differing mean equivalence ratio gradients within the flame brush. Since the local mixture fraction-progress variable alignment necessarily correlates with the mean mixture fraction-progress variable alignment, the observation that back-supported turbulent flames have higher burning intensity than front-supported turbulent flames can be explained by modified transport of heat and radicals from the products into the reaction zone due to the local flamenormal mixture fraction gradient, as observed in previous laminar flame studies [9].…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…the instantaneous flame front resides at approximately φ=0.7 in all cases) the difference in burning intensity is attributed to differing mean equivalence ratio gradients within the flame brush. Since the local mixture fraction-progress variable alignment necessarily correlates with the mean mixture fraction-progress variable alignment, the observation that back-supported turbulent flames have higher burning intensity than front-supported turbulent flames can be explained by modified transport of heat and radicals from the products into the reaction zone due to the local flamenormal mixture fraction gradient, as observed in previous laminar flame studies [9].…”
Section: Resultsmentioning
confidence: 57%
“…However the displacement speed shows an asymmetrical response to flame normal equivalence ratio gradients in both the laminar and turbulent cases, with back supported flames propagating faster compared to front-supported flames at a given tangential strain rate. The similar dependence of flame speed on flame-normal mixture fraction gradient in both the turbulent and laminar cases suggests that the phenomenon is due to the effect of molecular transport from the products that has been identified previously in laminar flame studies [9]. Figure 6 shows the mixture fraction-progress variable cross-dissipation rate = 2 ∇ξ∇c conditionally averaged on the sample-space variable for mixture fraction, .…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Later, the back support effect introduced in Ref. (3) was found to influence the flame dynamics (6), (8)- (9), (13)- (15) .…”
Section: Introductionmentioning
confidence: 99%
“…They showed that if the mean equivalence ratio of a mixture subjected to concentration fluctuations is higher than that of the lean flammability limit for a steady flame (a static flame), the lean flammability limit for a dynamic flame is lower than that for a static flame, and that as the mean equivalence ratio of the mixture approaches the lean flammability limit for the static flame, the lean flammability limit for the dynamic flame approaches that for the static flame. Numerical studies similar to those described above have been conducted to determine in detail the effect of the non-uniformity of the concentration on the flame propagation velocity (Richardson et al, 2010;Rahman et al, 2012;Zhou and Hochgreb, 2013;Miyamae et al, 2014;Shi et al, 2016;Zhang and Abraham, 2016).…”
Section: Introductionmentioning
confidence: 99%